THE INFORMATION SYSTEM OF ACEH CULTURE BASED ON ANDROID - Rahmi, Zulaida; Mahli, Zahrol (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
Culture is a medium that has a significant role in introducing and Characterizing the identify of a nation. The Aceh province has a unique culture and diverse. Some cultures that exist today are the result of acculturation between the malay culture, Middle East and Aceh. behind it all, the lack of information about the culture media in Aceh.Â  Make the public, especially young people have less interest in knowing about the culture. Research methods is modeling UML ( Unified Modeling Language). Result to be achieved is an Android- Based application Aceh Culture can increase our interest to preserve and conserve the culture of Aceh.Â Keywords: Culture, Android, Aceh